The Significance of Research Platforms for Future Advances in the Earth Sciences - Barnes, Christopher (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Abstract Scientific advances in recent decades in space exploration, satellite observations, and super computing have resulted in an ability to undertake global studies that were formerly impossible. The change in applied earth sciences from supporting the resource exploration sector to including the environmental conservation and protection sectorhas added new requirements for regional and global baseline environmental studies. Many new initiatives have been launched as international collaborative programs in which Canada — given its large land area and its front age on three oceans — has commonly had a special responsibility to play an important scientific role. The means by which such science is under taken has likewise adjusted tothese changes in the discipline. In particular, the need for sophisticated scientific research platforms has become essential. These range from space platforms (space stations, satellites), to atmospheric research platforms (balloons, aerosondes, mobile field stations), to ocean research platforms (ships, ice islands, tethered and autonomous underwater vehicles, drill ships),to continental research platforms (fieldstations, drilling platforms, seismic platforms). The management and funding of such research platforms is usually difficult and not well accommodated by institutions or granting agencies. The cost istypically more than can be recovered by user fees from individual researchers, yet below the special funding levels secured by some "big science" projects. It is argued that a new grant category {i.e., for NSERC grants) of Major Logistic Grants is required to balance the existing areas of support, such asEquipment Grants and Research (Oper-ating) Grants. This would provide notonly greater equity in proposed lines ofinquiry, but would allow for more cost-effective long-term planning of complex interdisciplinary international programs.